The Effect of Paired Down Passing Practice and Individual Drill Practice on Volleyball Down Passing Ability - Girsang, Dikky Fernando; Nofrizal, Dedi (Educational Sciences Journal, 2024)
This research aims to analyze the effect of training methods in improving the volleyball underpassing ability of male students at SMP Negeri 1 Pamatang Silimahuta. The two training methods tested were paired down passing drills and individual drills. This research uses a quasi-experimental method with a quasi-experimental design. The research sample consisted of 20 students selected by purposive sampling from a total population of 273 students. This research involved two experimental groups: the first group underwent pair down passing drills, while the second group took part in individual practice drills. Data analysis techniques were carried out using descriptive and inferential statistics, including t tests for dependent samples and independent samples. The results showed that the paired down passing training method significantly improved under passing ability with an average pre-test score of 24.50 which increased to 37.00 in the post-test (t count = 12.330, t table = 3.44). A comparison between the two methods shows that the paired down passing training method is more effective than the individual drill training method, with the calculation results (t count = 3.196, t table = 2.03) showing a significant difference. In conclusion, pair bottom passing drills have a greater impact on improving students' volleyball bottom passing abilities compared to individual drill drills.